Three artistic components Antabamba’s huaylía: Prose, Elegance and Gallantry - Sumi Arapa, Alfredo (2020)
This work has the purpose of determining whether the Huaylía is an expression of cultural resistance in the province of Antabamba. Knowing the culture of the Huaylia in Antabamba reinforces the national identity of the Apurímac region, since by not having a written memory about its past, its events and its daily life have been expressed in the dances. This research is basic in nature and the nature of the study explains the causes of its living presence in the province of Antabamba. The sample was made up of the waylía groups of Antabamba, the mayordomos of the year 2018 and 2019. The main result is the corroboration of the validity of many original cultural manifestations in Antabamba, the Mayura cultural stamp, the Huaylía. The latter is present in all its districts, with various peculiar characteristics of each district space. And it has three artistic components, the song or "prose", Costume or "elegance", the dance or "gallantry"